LINGUOCULTURAL FEATURES OF ONOMASTIC UNITS IN ENGLISH-LANGUAGE TOURISM TEXTS ABOUT UZBEKISTAN - Akhmedjonova Nigora Tohirovna (International Journal of Literature and Language Studies, 2026)
This article examines the linguocultural features of onomastic units used in English-language tourism texts about Uzbekistan. The study focuses on the semantic and pragmatic functions of toponyms, anthroponyms, and the names of historical and cultural sites that frequently occur in tourism discourse. Based on the analysis of English-language tourism materials, the role of onomastic units in representing Uzbekistan’s historical heritage, national values, and cultural identity to an international audience is identified. The findings reveal that onomastic units serve as an important means of shaping the country's tourism image and function as an effective tool of intercultural communication.